Influence of the type of dental trauma on the pulp vitality and the time elapsed until treatment: a study in patients aged 0-3 years - Pugliesi, DMC; Cunha, Robson Frederico [UNESP]; Delbem, ACB; Sundefeld, MLMM (Blackwell Munksgaard, 2004)
The purpose of the present study was to determine the influence of the type of trauma on the pulp vitality and the time elapsed until seeking dental care in children aged 0-3 years seen at the Baby Clinic of the Aracatuba Dental School, UNESP. A total of 1813 records were analyzed. Two hundred and three patients, corresponding to 302 traumatized teeth, were assessed clinically and radiographically. Hard-tissue injuries were the most frequent (52%), with a predominance of enamel crown fractures (41.4%), followed by concussions (12.6%) and intrusions (11.6%). Clinical and radiographic examination revealed that 72% of the traumatized teeth maintained pulp vitality. In the case of supporting-tissue lesions, 51.1% of the patients sought care within 1-15 days after injury, while in the case of hard-tissue injuries, 52.7% sought care only after 16 days. The results showed that supporting-tissue injuries had a significant influence on the faster seeking of dental care.
Keywords: dental trauma; primary teeth; dental luxation; crown fracture